Farelo de semente de goiaba na alimentação de suínos na fase inicial - Martins, Juliana Stocco (2019)
The objective of the study was to evaluate the nutritive value of guava seed meal (GSM) for piglets in the initial phase and the effects of increasing levels inclusion on animal performance, plasma parameters and diarrhea occurrence. In the experiment I, a digestibility test was carried out with 16 male commercial piglets, with a mean initial body weight of 14.64 ± 0.60 kg, distributed in a randomized complete block design, with two treatments, 8 replicates and one animal per experimental unit. Treatments consisted of a reference ration (RR) and a test ration with 20% RR replacement by GSM. In addition, GSM nutrient digestibility was determined by the feces and urine total collection method. In Experiment II, a performance test was carried out with 64 hybrid commercial line bred male piglets with mean initial body weight of 14.47 ± 2.09 kg and final weight of 24.03 ± 2.92 kg, distributed in a design in randomized blocks, with four treatments, four replicates and four animals per experimental unit. Treatments consisted of four GSM increasing levels inclusion in diet (0, 5, 10, and 15%). To determine the best GSM inclusion level in piglets diet in the initial phase, the final body weight (FBW), daily feed intake (DFI), weight daily gain (DGW), feed conversion (FC), urea (UR) and plasma glucose (GLU) concentrations, mean diarrhea score (MDS) and diarrhea incidence (DI) were evaluated. The results showed digestibility coefficients of 85.84% and 81.98% for DM and OM, 83.42 and 87.12% for CP and CE, 66.01% and 43.04% for NDF and ADF, respectively. The digestible nutrients values were 77.18%, 76.79%, 8.40%, 48.12% and 24.15% of DM, OM, CP, NDF and ADF respectively, presenting 3.275 kcal.kg-1 of digestible energy and 3.210 kcal.kg1 of apparent metabolizable energy. In the experiment II, there was a difference (P <0.05) for DFI, FC and UR, however there was no effect (P> 0.05) of initial body weight on FBW, DGW and GLU. For diarrhea occurrence, there was an effect (P <0.05) of treatments on MDS and DI scores, therefore GSM showed better MDS and DI reduction. In this context, it can be concluded that GSM can be used in the piglets feeding during the initial phase up to the level of 15% without compromising animal performance, parameters and diarrhea occurrence.